Penerapan Hukum Terhadap Pelaku Homo Seksual Di Bawah Umur: (Studi Kasus Putusan Nomor 377/Pid. Sus/2021/PN Nnk) - Ramadhani, Annisa Sabrina; Fakhlur, Fakhlur; Fattinudin, Muhammad (Postulat, 2024)
The perpetrators and victims of homosexual crimes in my research are adults and of the same gender. An adult who has sexual relations with a child means committing a criminal act, violating morals, and not being socially accepted because it is not considered normal. The author wants to conduct research by concentrating on the following issues: 1. How the law is used for the second crime of sexual violence. Nunukan District Court number 377/Pid.Sus/2021/PN. The author uses normative juridical research myths, a type of legal research that focuses on legal principles, rules, court decisions, and principles contained in laws and regulations. This method allows legal research to find and understand relevant legal substance and make strong legal arguments. The government must continue to review and update laws related to sexual violence to become more effective. This should be done to ensure that all types of sexual violence are clearly regulated and provide comprehensive protection, including adjusting provisions to meet the needs of society. In addition, the government should protect and assist victims of sexual violence by providing comprehensive medical and psychosocial services to help them recover, such as counseling, therapy, and good medical care. By following these suggestions, governments can strengthen the legal system, protect victims of sexual violence, and make the country fairer and safer.   Keywords : application of the law, seksual violence, obscenity, same